Pandemic (H1N1) 2009 Influenza Virus Infection in A Survivor Who Has Recovered from Severe H7N9 Virus Infection, China - Chen, Shan-Hui; Wu, Meng-Na; Qian, Yan-Hua; Ma, Guang-Yuan; Wang, Guo-Lin; Yang, Yang; Zhao, Teng; Lu, Bing; Ma, Mai-Juan; Cao, Wu-Chun (Frontiers in Microbiology, 2016)
We firstly report a patient who presented with severe complications after infection with influenza A(H1N1) pdm2009, more than one year after recovery from severe H7N9 virus infections. The population of patients who recovered from severe H7N9 infections might be at a higher risk to suffer severe complications after seasonal influenza infections, and they should be included in the high-risk populations recommended to receive seasonal influenza vaccination.